Routing approach for delay sensitive applications based on mobility prediction in mobile wireless sensor networks (2017)
In a Mobile Wireless Sensor Networks (MWSN) is possible the appearing of different factors related with dynamic networks, which generate no desirable delays in data transmission from source sensors to sinks. The main factors comprise sensors movement and energy consumption of sensors. The first factor affects the network performance in terms of delay since the sensors movement causes frequent connections and disconnections, which generates unstable communication paths in the network, affecting the delay in the network. The second factor represents the fact a sensor could deplete all of its energy causing breaking paths in the network, whereby it is necessary to establish a new path in order to reach a sink, at the expense of delaying the data transmission in the network. Given these factors, we want to propose distributed routing algorithms to guarantee the network delay requirements and minimizing the energy consumption of the network, taking into account a dynamic network...